COVID-19 Disruptions in Health Professional Education: Use of Cognitive Load Theory on Students' Comprehension, Cognitive Load, Engagement, and Motivation - Hadie, Siti Nurma Hanim; Tan, Vina Phei Sean; Omar, Norsuhana; Nik Mohd Alwi, Nik Aloesnisa; Lim, Hooi Lian; Ku Marsilla, Ku Ishak (Frontiers in Medicine, 2021)
This study explored the impact of online lectures that were developed using principles of cognitive load theory (CLT) and cognitive theory of multimedia learning (CTML) on health profession students’ lecture comprehension, cognitive load, cognitive engagement, and intrinsic motivation in learning. A total of 215 first-year undergraduate students in medical, dentistry, and nutrition programs participated in this pre-post quasi experimental study. The students attended a typical face-to-face lecture on Day-1 of the intervention, followed by a CLT-based online lecture eight weeks thereafter. Their comprehension of the lecture topics was measured through pre- and post-lecture assessments, and their cognitive load, cognitive engagement, and motivation were measured immediately after each lecture session. The analysis revealed that the CLT-based online lectures promoted the students’ comprehension of the lecture content (p <0.001), self-perceived learning (p <0.001), engagement toward the learning material, and motivation to learn (p = 0.025). It was also effective at reducing the students’ intrinsic and extraneous cognitive loads (p <0.001), Hence, designing online lectures using CLT and CTML principles could be an effective method to promote students’ knowledge and comprehension, cognitive engagement, and learning motivation. However, further research is needed to investigate the applicability and impact of CLT-based online lectures in non-health profession disciplines.